Functional and Radiological Outcome of Minimal Invasive Plate Osteosynthesis for Fractures of Tibia (Journal of Pakistan Orthopaedic Association, 2014)
Objective: To determine the outcome of closed proximal and distal tibia fractures managed by minimal invasive plate osteosynthesis (MIPO).Material and Methods: This descriptive study of 18 patients was conducted from June 2013 to May 2014. In this study all patients with AO type 42B1-3, 42C1-3 and 43A1-3 of adult age and either sex were included, while patients with open fracture, poly trauma patient and patients with associated neurovascular injuries were excluded. Functional outcome of the procedure was measured in terms of Range of motion (ROM) and fracture healing time.Results: Total of 18 patients was included of which 13 were male and 5 were female. Age ranged from 22 to 57 years. In more than 90% of the patients the functional outcome of the procedure was excellent. There was one complication and there was no mortality in the series.Conclusion: MIPO is a very effective procedure for the treatment of proximal and distal tibial fractures. It is effective irrespective of the age of the patient and mode of injury.Key words: Minimal Invasive Plate Osteosynthesis (MIPO), Tibial Fracture, and Functional outcome.